Peranan Promosi dalam Meningkatkan Pengetahuan dan Pemakaian Produk Studi Kasus Produk Power Fuel pada PT Elnusa Petrofin - Sujana, Sujana; Aminarti, Dewi (Jurnal Ilmiah Ranggagading (JIR), 2007)
The purpose of this research is to analyze how far the effect which implemented by the company in marketing and communication of the product to consumer. This analysis was doing to know consumer who have consumed additive on grade of knowledge and additive consumption in every refueling . Research is done by using Multi Correspondent Analysis (MCA) , a technique of multidimensional scale for qualitative scale data in marketing research. Correspondent analysis could give the information of characteristic from every selection attribute which shown by two dimension map. Result have shown based on analysis from the both of promotion data in personal selling and direct marketing, have a different type because on personal selling have strong effect in every attribute where the average number of index value is 68,8% and direct marketing has strong effect in every attribute, where the average number of index value is 66,6%. Keywords : Knowledge grade, usage